Wheat Kernel Variety Identification Based on a Large Near-Infrared Spectral Dataset and a Novel Deep Learning-Based Feature Selection Method - Zhou, Lei; Zhang, Chu; Taha, Mohamed Farag; Wei, Xinhua; He, Yong; Qiu, Zhengjun; Liu, Yufei (Frontiers in Plant Science, 2020)
Near-infrared (NIR) hyperspectroscopy becomes an emerging non-destructive sensing technology for inspection of crop seeds. A large spectral dataset of more than 140,000 wheat kernels in thirty varieties was prepared for classification. Feature selection is a critical segment in large spectral data analysis. A novel convolutional neural network-based feature selector (CNN-FS) was proposed to screen out deeply target-related spectral channels. A convolutional neural network with attention (CNN-ATT) framework was designed for one-dimension data classification. Popular machine learning models including support vector machine and partial least square discrimination analysis were used as the benchmark classifiers. Features selected by conventional feature selection algorithms were considered for comparison. Results showed that the designed CNN-ATT produced a higher performance than the compared classifier. The proposed CNN-FS found a subset of features, which made a better representation of raw dataset than conventional selectors did. The CNN-ATT achieved an accuracy of 93.01% using the full spectra, and keep its high precision (90.20%) by training on the 60-channel features obtained via the CNN-FS method. The proposed methods have great potential for handling the analyzing tasks on other large spectral datasets. The proposed feature selection structure can be extended to design other new model-based selectors. The combination of NIR hyper spectroscopic technology and the proposed models has great potential for automatic non-destructive classification of single wheat kernels.